ChemInform Abstract: Synthesis and Biological Evaluation of Substituted 2‐Anilino‐7H‐pyrrolopyrimidines as PDK1 Inhibitors. Issue 51 (23rd December 2014) - O'Brien, Nathan J.; Brzozowski, Martin; Wilson, David J.D.; Deady, Leslie W.; Abbott, Belinda M.
Abstract Title compounds (V) are synthesized via sequential Suzuki coupling of dichloro‐pyrrolopyrimidine (I) with boronate (II) followed by Buchwald—Hartwig cross‐coupling with various customized anilines (IV).